Peningkatan Kemampuan Literasi Kimia dan Efikasi Diri melalui Pendekatan Berbasis Konteks dengan Strategi Prediksi-Observasi-Eksplanasi - Sandra Desfa Jayanti; Hari Sutrisno (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the low levels of chemical literacy and student self-efficacy by implementing a context-based learning approach using the Prediction–Observation–Explanation (POE) strategy. The research aimed to assess the differences and effective contributions of chemical literacy and self-efficacy before and after the intervention, and to compare students taught with the POE-based approach versus those using a scientific approach. A quantitative method was used with a quasi-experimental design, including both dependent pre-test and post-test without a control group, and independent pre-test and post-test with a control group. The sample consisted of four randomly selected 11th-grade classes. Instruments included 10 chemical literacy pre-test items, 9 post-test items, and 23 self-efficacy questionnaire items focused on the Thermochemistry unit. Data were analyzed using Paired Sample T-tests and Independent Sample T-tests. Results showed a significant improvement in chemical literacy after implementing the POE strategy, confirming its effectiveness in enhancing conceptual understanding. However, student self-efficacy did not show a statistically significant change, although a slight positive trend was observed. The study concludes that while the POE strategy effectively enhances chemical literacy, it is insufficient for improving self-efficacy, suggesting the need for more sensitive measurement tools and additional strategies to support affective learning outcomes.